Cytopathic Effects Incited by Viroid RNAs and Putative Underlying Mechanisms - Di Serio, Francesco; De Stradis, Angelo; Delgado, Sonia; Flores, Ricardo; Navarro Ramirez, Beatriz (Frontiers in Plant Science, 2013)
Viroids are infectious agents identified only in plants so far. In contrast to viruses, the genome of viroids is composed of a tiny circular RNA (250–400 nt) not coding for proteins, but containing in its compact structure all the information needed for parasitizing the transcriptional and RNA trafficking machineries of their hosts. Viroid infections are frequently accompanied by cellular and developmental disorders that ultimately result in macroscopic symptoms. The molecular events linking the structural domains of viroid RNAs with cellular and macroscopic alterations remain largely unexplored, although significant progress has been lately achieved in one specific viroid-host combination, highlighting the ability of viroids to strongly interfere with their host RNA regulatory networks. Cytopathic effects induced by nuclear-replicating viroids, which were investigated since early studies on viroids, consist in irregular proliferations of cell membranes (paramural bodies or plasmalemmasomes), cell wall distortions, and chloroplast malformations. Different alternatives have been proposed regarding how these cytological alterations may influence the onset of macroscopic symptoms. Recently, the cytopathology and histopathology incited by a chloroplast-replicating viroid have been investigated in depth, with defects in chloroplast development having been related to specific molecular events that involve RNA silencing and impairment of chloroplast ribosomal RNA maturation. On this basis, a tentative model connecting specific cytopathologic alterations with symptoms has been put forward. Here, early and more recent studies addressing this issue will be reviewed and reassessed in the light of recent advances in the regulatory roles of small RNAs.